STUDY OF NUTRITIONAL CONTENTS OF SEA URCHIN GONAD FROM DRINI BEACH, GUNUNG KIDUL, YOGYAKARTA - Delianis Pringgenies; Richardus Mahatmada Indrajati; Ali Djunaedi (Jurnal Kelautan, 2020)
ABSTRACTThis paper aims to determine the types and contents of protein, fatty acids, amino acids and protein in the gonads of Arbacia lixula, Colobocentrotus atratus, Heterocentrotus trigonarius and Echinotrix diadema from the waters of Drini, Gunung Kidul, Yogyakarta. Kjedal method was used to analyze the protein content, while GC and HPLC methods were employed to analyze amino acids in this study. The results showed that the protein contents of each sample, consequently from highest to lowest, were Heterocentrotus trigonarius (13.3 %), Echinotrix diadema (10.86), Colobocentrotus atratus (10.41) and Arbacia lixula (9.90%). Amino acids analysis from all identified both saturated fatty acids, consisting of lauric acid, myristic acid, palmitic acid, stearic acid, arachidonic acid, lignoceric acid, as well as non-saturated fatty acids, consisting of palmitoleic acid, oleic acid, linoleic acid, erucic acid, EPA, and DHA. The highest contents of non-saturated fatty acids were identified in Colobocentrotus atratus (434.14 mg/100g) and the lowest content in Arbacia lixula (197.71 mg/100g). The highest percentage of essential fatty acids was found in Heterocentrotus trigonarius (0.29%), whereas the lowest was found in Echinotrix diadema (0.19 %). It is concluded that the gonad of Heterocentrotus trigonarius showed the highest protein and essential fatty acids contents. This study also found that Colobocentrotus atratus sea urchin gonads possess the highest content of non-saturated fatty acids (434.14 mg/100g).  Keywords: amino acid, fatty acid, protein, sea urchin gonad.